Desenvolvimento de armadilha para captura de triatomíneos e pesquisa das amostras capturadas em engenhos de cana-de-açúcar - Oliveira, Ismael Vinicius de (Universidade Federal Rural do Semi-Árido, 2021)
Chagas disease is a tropical pathology characterized as endemic in several countries. Among the forms of transmission are vectorial, transfusion, gestational, transplantation, laboratory accidents and the oral route, which stands out in a new scenario associated with the outbreak of infection. Some foods are related to oral transmission with emphasis on açaí and sugar cane. In this context, the objective of this work was to develop a trap and to research triatomines associated with the diagnosis of Trypanosoma cruzi in the captured vectors and in sugar cane juice from sugar cane mills. During a one-year period, 100% (3/3) of the active sugar cane mills in the study area were surveyed, where the vectors were searched, the juice collected during the milling period and T. cruzi researched. The capture of the triatomines by passive search occurred through a trap developed with technological characteristics, sustainable and installed in the peridomicile of the mills. While the active search was carried out through thorough inspection in intra and peridomicile areas. The research for T. cruzi was carried out in the feces of engorged triatomines, as well as in the sugar cane juice in natura, where five samples per mill were collected, totaling 15 samples analyzed. The results showed that the trap developed was efficient, resulting in two patent applications with registration numbers for the trap (BR 102021001360-5) and software (BR 512021000167-2). As for collection data, it was observed that in 100% (3/3) of the mills hematophagous triatomines were captured, totaling 22 vectors, 41% (9/22) by passive search and 59% (13/22) by active search. As for the environment, the insects were found in 81.8% (18/22) of the peridomestic and 18.2% (04/22) intradomestic areas. 81.8% (18/22) adults and 18.2% (04/22) nymphs were identified, with one adult and the nymphs not identifiable. Two species were identified, being 68.18% (15/22) Triatoma brasiliensis and 9.09% (02/22) Triatoma pseudomaculata. For the diagnosis of T. cruzi in triatomines, 4.55% (1/22) were positive and 95.45% (21/22) negative. As for the broth, 100% (15/15) of the samples were negative for the presence of T. cruzi, however, in 33.3% (5/15) the presence of dirt (microplastics) was observed. In conclusion, the development of modern traps for vector research was relevant, with capture and positivity of hematophagous triatomines associated with the presence of dirt in the broth. Demonstrating the importance of investigation and monitoring of sites with the possibility of oral transmission, which currently represent the majority of infection records in Brazil
Keywords: Doença de Chagas; Infecção por alimentos; Barbeiros; Chagas Disease; Foodborne Infection; Barbers; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE